Meningkatkan kemampuan passing bawah bolavoli menggunakan metode bermain - Atsani, Muhammad Reza (Edu Sportivo: Indonesian Journal of Physical Education, 2020)
This study aims to improve the ability of passing volleyball under class XI Mekatronika EPCOS SMK Negeri 1 Batam through the playing method. This type of research uses classroom action research. The subjects of this study were 20 people consisting of 13 male students and 7 female students. The research instrument used a rubric for the assessment of the volleyball passing performance. The results showed that there was an increase in conducting this research, so it was concluded that the playing method could improve the volleyball under-passing ability of class XI Mekatronika EPCOS SMK Negeri 1 Batam. It is hoped that this research can serve as a reference for the future or a reference in the teaching and learning process.